Astrocyte transport of glutamate and neuronal activity reciprocally modulate tau pathology in Drosophila. - Kilian, J.G.; Hsu, H.W.; Mata, K.; Wolf, F.W.; Kitazawa, M. (Neuroscience, 2017)
Abnormal buildup of the microtubule associated protein tau is a major pathological hallmark of Alzheimer's disease (AD) and various tauopathies. The mechanisms by which pathological tau accumulates and spreads throughout the brain remain largely unknown. Previously, we demonstrated that a restoration of the major astrocytic glutamate transporter, GLT1, ameliorated a buildup of tau pathology and rescued cognition in a mouse model of AD. We hypothesized that aberrant extracellular glutamate and abnormal neuronal excitatory activities promoted tau pathology. In the present study, we investigated genetic interactions between tau and the GLT1 homolog dEaat1 in Drosophila melanogaster. Neuronal-specific overexpression of human wildtype tau markedly shortened lifespan and impaired motor behavior. RNAi depletion of dEaat1 in astrocytes worsened these phenotypes, whereas overexpression of dEaat1 improved them. However, the synaptic neuropil appeared unaffected, and we failed to detect any major neuronal loss with tau overexpression in combination with dEaat1 depletion. To mimic glutamate-induced aberrant excitatory input in neurons, repeated depolarization of neurons via transgenic TrpA1 was applied to the adult Drosophila optic nerves, and we examined the change of tau deposits. Repeated depolarization significantly increased the accumulation of tau in these neurons. We propose that increased neuronal excitatory activity exacerbates tau-mediated neuronal toxicity and behavioral deficits.